Menstruation: A Silent Harassment among Women and Girls - Shrestha, Abina (Bagiswori Journal, 2022)
This paper tries to address one of the cultural taboos related with menstruation existing and in practice in Nepalese society, creating an incident of social harassment for women and girls, in a silent mode, in the name of social norms. A methodology of unstructured one to one interview and a group discussion were employed to dig inside the issue which ends up with the remark of being in intimidation, annoyance, hassle, stigmatize, discriminate, and other ill-practices. This write-up might contribute to re-think on harmful menstruation practices in order to bring positive change in cultural practice and making menstruation talk more open in society.